A JUSTIÇA EM PAUTA: O Poder Judiciário Brasileiro na Mídia Impressa - Ferreira, Maira Pereira (2009)
The research was carried out in the main Brazilian printed media, between the months of July and December of 2007, in order to verify the image of the Brazilian Judiciary Power disclosed by the media, interpreting the main themes approached in the publications and angu-lation of the subject-matters. The content analysis and the media image auditing tool were used. The research concluded that the printed media focuses on the Brazilian Judiciary Power mainly when it analyses legal proceedings that involve public persons, especially parliamen-tarians. It was also observed that the majority of the published subjects mentioned acts of the Supreme Court, which is the highest instance of the Brazilian judicial system and is responsi-ble for placing senators on trial, who are the main focus of the publications, and of authorities with the right to special venue. Besides this it was concluded that the majority of the subject-matters refer to legal proceedings still under judgment, proving the there is no frequent fol-low-up of the decisions and judgments of the judiciary power. In spite of the fact that the analysis refers to a delimited period, the faulty communication within the judiciary power was evident and suggestions were presented to improve the mentioned communication.(AU)